Prevalencia de algunas enfermedades infecciosas en bovinos de resguardos indígenas del Cauca, Colombia, 2017 (2018)
The Cauca region in Colombia has indigenous reservations that have presented different problems associated with the armed conflict, which has limited the entities to carry out bovine disease control programs. Therefore, the aim of this work was to determine the prevalence of some infectious diseases of reproductive traits in cattle of three indigenous resguards in Cauca, 2017. Blood samples of 30 cows were collected to determine the prevalence of Neospora caninum, Brucella abortus, bovine viral diarrhea (BVD), Infectious bovine rhinotracheitis (IBR) and Leptospira sp. serovars Hardjo prajitno, bovis and Pomona. The tests were performed by ELISA, rose bengal and microscopic agglutination. Using R software, a descriptive analysis was carried out and the frequencies for each disease were estimated. In addition, co-infections between diseases were estimated and a logistic regression model was performed to determine the effect of the herd, reservation, racial component, age group, number of animals and size of the farm on the disease positivity. The prevalence was N. caninum 36%, BVD 60%, IBR 30%, B. abortus 0%, Leptospira spp. serovars Hardjo prajitno 26%, Hardjo bovis 12%, y Pomona 10%. According to the risk anal-ysis, the seropositivity for BVD and IBR were associated with the place where the animals lived, in this case Tacueyó, but this was directly related to the size of the herds, since the greater, the area more animals were positive. In general, it was found that the situation in the region is similar to that of other sites in Colombia.